2019
DOI: 10.5400/jts.2012.v17i1.9-17
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid and Water Management to Decrease Ferro (Fe2+) Solution and Increase Productivity of Established New Rice Field

Abstract: The purpose of this research was to gain a technological breakthrough in controlling Fe toxicity (Fe2+) on Ultisol in a new established rice field by using humic acid from rice straw compost and water management, so that optimal production of rice plants could be achieved. The experiment was designed using a 2 × 4 factorials with 3 replications in a split plot design. The main plot was water management consists of 2 levels: continuous and intermittent irrigation (2 weeks flooded and 2 weeks field cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The introduction of HAs also resulted in a significant increase in soil pH, which further reduced the mobility and bioavailability of iron. Similar results were reported by Herviyanti et al [95], who evaluated the effect of HAs applications (200-600 mg kg −1 ) on the iron content of flooded soils and the yield quality of rice. They obtained the best results in the series with the highest HA dose.…”
Section: Discussionsupporting
confidence: 88%
“…The introduction of HAs also resulted in a significant increase in soil pH, which further reduced the mobility and bioavailability of iron. Similar results were reported by Herviyanti et al [95], who evaluated the effect of HAs applications (200-600 mg kg −1 ) on the iron content of flooded soils and the yield quality of rice. They obtained the best results in the series with the highest HA dose.…”
Section: Discussionsupporting
confidence: 88%
“…Rezki, Ahmad, & Gusnidar (2007) reported that Sub-bituminous coal taken from Pasaman, West Sumatra can be used as a source of organic material because it contains HS Copyright © 2019 Universitas Brawijaya as much as 31.5% (21% humic acid and fulvic acid 10.5%) and were extracted with 0.5 N NaOH. Subbituminous coal percentage humic acid (21%) was higher than the percentage of humic acid contained from other organic materials, such as municipal solid waste compost (1.4%), manure (1.6%), rice straw compost (5%), and peat soil (9.2%) (Herviyanti, Prasetyo, Ahmad, & Saidi, 2012). Therefore, the Sub-bituminous coal as a source of HS can be used as soil organic matter to improve soil fertility.…”
Section: Introductionmentioning
confidence: 95%
“…The aplication of HS has been studied by Herviyanti, Prasetyo, Ahmad, & Saidi (2012) from the first year of research. The result showed that the highest grain yield of paddy rice was on the treatment of 800 ppm HS (1.6 t/ha) + 100% P-fertilizer recommendation (300 kg/ha) which were incubated with I 3 (the mixture of HS and P fertilizer for 1 week and then incubated to the soil for 1 week) with grain yield 5.27 t/ha.…”
Section: Introductionmentioning
confidence: 99%
“…The redox reaction is raised by poor drainage, deficiency of K, Ca, Mg, P, Zn, and Mn, as well as a low amount of soil oxygen. Newly opened rice fields that were infected by ferro toxicity can be recovered through proper water management, amelioration, fertilization, adjustment of planting time, and the use of tolerable crop varieties (Herviyanti et al, 2019).…”
Section: Characteristics Of Research Areasmentioning
confidence: 99%